Strategi Pemulihan Usaha Meubel Pasca Bencana alam PASIGALA 2018 - Muhammad Afandi; Isna Tuainia; Deswita Wulandari; Nurfadhila Lapangandong; Suasa Suasa; Dandan Haryono; Nurhayati Hamid (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The 2018 natural disaster in Palu, Sigi, and Donggala (PASIGALA) caused significant losses in the furniture industry, including infrastructure damage, supply chain disruptions, and loss of livelihoods. This study aims to formulate sustainable recovery strategies for the sector through observations and in-depth interviews. The findings highlight key challenges such as facility damage, asset loss, limited capital, and raw material shortages. Recovery strategies include infrastructure repair, access to funding, product diversification, digital marketing, and community empowerment. Support from the government and financial institutions, including financial aid and training, has been critical to recovery success. Signs of recovery are evident through increased production and sales, although raw material supply remains a pressing issue. This study provides strategic recommendations to rebuild a resilient and sustainable furniture industry while contributing to more inclusive and adaptive recovery policies for future disaster resilience.